Membantu Mengatasi Kecemasan pada Anak Usia Dini - Fikri Fadilatul Ikhsan (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
Anxiety in early childhood is a complex issue that can significantly affect children's emotional, social, and academic development. This article aims to discuss the causes, effects, and management strategies for anxiety in children, based on a review of recent theories and research. The writing method employed includes a literature review referencing current studies and theories from experts in Indonesia. The discussion reveals that anxiety in children can be triggered by genetic factors, an unstable family environment, and traumatic experiences. Its impacts include disruptions in emotional development, limited social skills, and poor academic performance. To address these issues, this article recommends several strategies, including creating a safe environment, providing emotional education, implementing relaxation techniques, and encouraging open communication and engagement in social activities. With a comprehensive understanding and the application of appropriate strategies, it is hoped that children can overcome their anxiety and grow into healthier emotional and social individuals.